(E)-1-(2-Hydroxy-3,4-dimethoxyphenyl)-3-(4-hydroxyphenyl)-prop-2-en-1-on e - Krishna, J. R.; Kumar, N. J.; Krishnaiah, M.; Rao, C. V.; Rao, Y. K.; Puranik, Vedavati G. (Acta Crystallographica Section E-Structure Reports Online, 2005)
The title compound, C17H16O5, crystallizes with two independent molecules in the asymmetric unit. These are oriented approximately orthogonal to one another. The keto group adopts an s-cis conformation; the six-membered ring formed by the O-H&BULL;&BULL;&BULL; O hydrogen bond and the adjacent benzene ring are approximately coplanar. In addition to an intramolecular O-H&BULL;&BULL;&BULL; O hydrogen bond, intermolecular O-H&BULL;&BULL;&BULL; O interactions link adjacent molecules into chains.

Effect of 2-(2-pyridyl)azole-based ancillary ligands (L1-4) on the electrophilicity of the nitrosyl function in [Ru-II(trpy)(L1-4)(NO)](3+) [trpy=2,2 `: 6 `,2 `'-terpyridine]. synthesis, structures, and spectroscopic, electrochemical, and kinetic aspects - Chanda, N.; Paul, D.; Kar, S.; Mobin, Shaikh M.; Datta, Anindya; Puranik, Vedavati G.; Rao, K. K.; Lahiri, Goutam Kumar (Inorganic Chemistry, 2005)
Ruthenium nitrosyl complexes [Ru(trpy)(L1-4)(NO)](3+) (13-16) [trpy = 2,2':6',2"-terpyridine, L-1 = 2-(2-pyridyl)-benzoxazole, L-2 = 2-(2-pyridyl)benzthiazole, L-3 = 2-(2-pyridyl)benzimidazole, L-4 = 1-methyl-2-(2-pyridyl)-1H-benzimidazole] were obtained in a stepwise manner starting from [Ru-II(trpy)(L1-4) (Cl)]ClO4 (1-4) &RARR; [Ru-II(trpy)(L1-4) (H2O)](ClO4)(2) (5-8) &RARR; [Ru-II(trpy)(L1-4) (NO2)ClO4 (9-12) &RARR; [Ru-II(trpy)(L-1,L-2,L-4) (NO)](ClO4)(3) (13, 14, 16)/[Ru-II(trpy)(L-3) (NO)](Cl)(4))(2)(NO3) (15). Crystal structures of 1, 2, 4, 9, 12, 13, 15, and 16 established the stereoretentive nature of the transformation processes. Though the complexes of L1, L3, and L 4 were isolated in the isomeric form A (π-acceptor trpy and azole ring in the equatorial plane and the pyridine and chloride donors in the axial positions), complexes of L 2 preferentially stabilized in form B (trpy and pyridine in the equatorial plane and the azole ring and chloride donors in the axial positions). The v(NO) stretching frequency varied in the range of 1957-1932 cm(-1), 13 &MGT; 14 &MGT; 15 > 16, primarily depending on the electronic aspects of L as well as the isomeric structural forms. The coordinated nitrosyl function underwent successive reductions of [Ru-II-NO+](3+) &RARR; [Ru-II-NO&BULL;](2+) and [Ru-II-NO&BULL;](2+) - [Ru-II-NO-](+), and the first reduction potential follows the order 14 > 13 &MGT; 15 &AP; 16. The nearly axial EPR spectra having nitrogen hyperfine splittings (A &AP; 26 G) at 77 K of 13(-)-16(-) with (g) &AP; 2.0 established that the reduction process is largely centered around the nitrosyl function. Despite an appreciably high v(NO), the complexes were found to be unusually stable even in the aqueous medium. They transformed slowly and only partially into the corresponding nitro derivatives in H2O (k &AP; 10(-4) s(-1) and K = 0.4-3.8). The chloro (1-4), aqua (5-8), and nitro (9-12) derivatives displayed reasonably strong emissions near 700 nm at 77 K (φ = 10(-1)-10(-2)). The aqua derivative 7 was found to interact with the calf thymus and the circular form of p-Bluescript SK DNA.

Efficient synthesis of azetidine-2,3-diones from L-(+)-diethyl tartrate - Chincholkar, Pinak M.; Puranik, Vedavati G.; Deshmukh, Abdul Rakeeb A. S. (Synlett, 2007)
A convenient route to enantiopure azetidine-2,3-diones is described. The chiral ketene generated from commercially available L-(+)-diethyl tartrate on Staudinger cycloaddition with different imines gave spiro-beta-lactams in good yields. These spiro-beta-lactams were transformed into azetidine-2,3-diones in excellent yields in a two-step process.
Keywords: Cycloaddition; imines; lactams; spiro compounds; stereoselective synthesis

Effect of the allylic substituents on ring closing metathesis: the total synthesis of stagonolide B and 4-epi-stagonolide B - Giri, Awadut G.; Mondal, Mohabul A.; Puranik, Vedavati G.; Ramana, Chepuri V. (Organic & Biomolecular Chemistry, 2010)
The total syntheses of stagonolide B and its 4-epimer were carried out to probe into how the relative stereochemistry of allylic hydroxy groups and their protecting groups influence the efficiency of the ring closing metathesis.

Enantioselective total syntheses of (-)-isonitramine, (-)-sibirine, and (+)-nitramine by ring-closing metathesis - Pandey, Ganesh; Kumara, Prasanna C.; Burugu, Shiva Kumar; Puranik, Vedavati G. (European Journal of Organic Chemistry, 2011)
Concise enantioselective total syntheses of naturally occurring 2-azaspiro[5,5]undecan-7-ol (Nitraria) alkaloids viz. ()-isonitramine, ()-sibirine, and (+)-nitramine are accomplished in 42, 38, and 25?% overall yield, respectively, in six steps starting from enantiomerically pure (S)-methyl 3-allyl-2-oxo-1,2,3,6-tetrahydropyridine-3-carboxylate (>99?%?ee). The key feature of the syntheses involves diastereoselective HosomiSakurai allylation followed by ring-closing metathesis.
Keywords: Alk-aloids; Allylation; Amino alcohols; Metathesis; Total synthesis

Efficient total synthesis of calothrixin B - Bhosale, Shrikar M.; Gawade, Rupesh L.; Puranik, Vedavati G.; Kusurkar, Radhika S. (Tetrahedron Letters, 2012)
An efficient synthesis of calothrixin B (2) is demonstrated starting from 9H-carbazol-4-ol, having two one-pot reaction sequences as key steps. As a novel observation, DMF-methanol was shown to be a hydride donor for reduction of aldehyde to alcohol. Unexpectedly, nucleophilic substitution of benzyloxy by methoxy group was observed. (C) 2012 Elsevier Ltd. All rights reserved.
Keywords: Calothrixin B; CAN; DMF-methanol; Hydride donor

Ester vs. amide on folding: a case study with a 2-residue synthetic peptide - Vijayadas, Kuruppanthara N.; Nair, Roshna V.; Gawade, Rupesh L.; Kotmale, Amol S.; Prabhakaran, Panchami; Gonnade, Rajesh G.; Puranik, Vedavati G.; Rajamohanan, Pattuparambil R.; Sanjayan, Gangadhar J. (Organic & Biomolecular Chemistry, 2013)
Although known for their inferiority as hydrogen-bonding acceptors when compared to amides, esters are often found at the C-terminus of peptides and synthetic oligomers (foldamers), presumably due to the synthetic readiness with which they are obtained using protected peptide coupling, deploying amino acid esters at the C-terminus. When the H-bonding interactions deviate from regularity at the termini, peptide chains tend to ``fray apart''. However, the individual contributions of C-terminal esters in causing peptide chain end-fraying goes often unnoticed, particularly due to diverse competing effects emanating from large peptide chains. Herein, we describe a striking case of a comparison of the individual contributions of C-terminal ester vs. amide carbonyl as a H-bonding acceptor in the folding of a peptide. A simple two-residue peptide fold has been used as a testing case to demonstrate that amide carbonyl is far superior to ester carbonyl in promoting peptide folding, alienating end-fraying. This finding would have a bearing on the fundamental understanding of the individual contributions of stabilizing/destabilizing non-covalent interactions in peptide folding.

Efficient method for the synthesis of quinoxaline derivatives catalyzed by titanium silicate-1 - Chandrachood, Pranav S.; Jadhav, Amol R.; Garud, Dinesh R.; Deshpande, Nirmala R.; Puranik, Vedavati G.; Kashalkar, Rajashree V. (Research on Chemical Intermediates, 2020)
A series of quinoxaline derivatives were efficiently synthesized by convenient and simple procedure in excellent yields using 1 wt.% of titanium silicate (TS-1) catalyzed reaction of 1,2-diamines and 1,2-diketones in methanol at room temperature. This reaction is scalable to multigram scale and the catalyst is recyclable. [GRAPHICS] .
Keywords: 2-Diketones; Aromatic 1; o-Phenylenediamine; Quinoxaline; Room temperature; Titanium silicate-1